Prosthetic complications of fixed dental prostheses supported by locking-taper implants: a retrospective study with a mean follow-up of 5 years - Wen mo Gao; Wei Geng; Chen chen Luo (BMC, 2021)
Abstract Background Restoration with locking-taper implants is a widely used methodology. However, conical connection systems such as locking-taper implant systems have rarely been examined. This study provides a retrospective investigation of locking-taper fixed restorations, mainly focusing on prosthetic complications. Methods Patients undergo treatment with conical connected implants from 2008 to 2010 were examined. Preparation of the implant sites was performed according to the standard procedures for the Bicon system. Bone healing took over 6 months, and the prosthetic procedure was initiated thereafter. Integrated abutment crowns or gold porcelain crowns were used, and the prosthesis type was a single crown or a fixed dental prosthesis. Once the crown was in place, its occlusion was thoroughly checked and adjusted, and then the crown was glazed or finely polished. The Kaplan-Meier method was used to calculate the cumulative complication-free rates for 5 and 10 years. Additionally, a Cox regression model was used to identify the factors that independently influenced the results. Implant survival and marginal bone loss were also investigated. Results A total of 392 patients who underwent 541 implants and 434 locking taper implant-based restorations from 2008 to 2010 were examined. The overall 5-year cumulative complication-free rate was 83.34%. The most common prosthetic complication was veneer chipping, with a frequency of 67.53%. According to the Cox regression model, the complication-free rate of integrated abutment crowns was significantly higher than that of gold porcelain crowns, that of molar regions was significantly higher than that of premolar regions, and that of females was significantly higher than that of males. Only three implant failures happened, and the mean marginal bone loss values at 1- year, 5-years and 10- years were 0.25 mm (95% CI ± 0.12), 0.40 mm (95% CI ± 0.03) and 0.51 mm (95% CI ± 0.05), respectively. Conclusion Veneer chipping was the most common complication with locking-taper implant-supported fixed restorations. The incidence of complications for IACs is significantly higher than that for GPCs. Age, location, and prosthesis type are not determinants of prosthetic complications. Besides, the long-term clinical effect of locking-taper implant can meet the clinical needs. The bone tissue level around the implant can maintain long-term stability.